ACOLHIMENTO A MULHERES EM SITUAÇÃO DE VIOLÊNCIA FAMILIAR E REALIZAÇÃO DE PESQUISA - Campos, Fabiana d.; Fonseca, Gabriela S. d.; Dill, Janice C.; Soares, Flávia G.; Ávila, Patricia M. d.; Lenhardt, Carise (Salão do Conhecimento, 2013)
Resumo